Optimalisasi Produksi Air Tawar: Identifikasi dan Efisiensi pada Reverse Osmosis Plant di MV Golden Splendor - Iqbal Alansyah, Fardian; Oscar, Yulius; Noviarianto, Noviarianto; Nuriyanis, Akhmad (PPPM Polimarin, 2025)
The Reverse Osmosis Plant (RO) is a critical system for supplying freshwater on board ships to meet accommodation and operational needs. This study aims to identify the causes of reduced freshwater production in the RO Plant aboard the MT. Golden Splendor and to propose optimization strategies. A qualitative approach was employed through direct observation, interviews with engineering officers, and analysis of logbook data collected during a 12-month sea training period. The findings indicate that the main causes of inefficiency include clogged filters and membranes, leakage in the ejector pump, and inadequate routine maintenance. These issues led to a decline in freshwater production from 1000 liters/hour to 700 liters/hour. After corrective measures such as filter replacement, membrane cleaning, and pump repairs were implemented, production increased back to 1000 liters/hour. The results highlight the importance of scheduled maintenance and system monitoring to ensure optimal RO performance. The study recommends strict adherence to maintenance procedures and enhanced system supervision to improve efficiency and ensure the sustainability of freshwater production on board.